Factors associated with the duration of breastfeeding in mothers of babies cared for in a kangaroo family program - Giraldo-Marín, Isabel-Cristina; Henao Murillo, Natalia Andrea; Londoño Rodríguez, María Camila; Aguirre Torres, Manuela; López Palacio, Gabriel Jaime (Investigación y Educación en Enfermería, 2023)
Goal. To determine the factors associated with the duration of breastfeeding in mothers of babies cared for in a kangaroo family program. Methods. Quantitative, observational study with a secondary source of a retrospective cohort of 707 babies with monitoring at admission, at 40 weeks, at three and at six months of corrected age in the kangaroo family program of a public hospital in the municipality of Rionegro (Antioquia, Colombia) from 2016 to 2019. Results. 49.6% of babies were born with low weight for gestational age and 51.5% were female. 58.3% of the mothers were unemployed and 86.2% of them lived with their partner. When entering the kangaroo family program, 94.2% of the babies received breastfeeding and at six months they were 44.7%. The variables that were associated with the duration of breastfeeding up to six months according to the explanatory model were: the mother's cohabitation with her partner (adjusted prevalence ratio - APR: 1.34) and receiving breastfeeding when entering the kangaroo family program (APR: 2.30). Conclusion. The factors related to the duration of breastfeeding in mothers of babies cared for in the kangaroo family program were that the mother lived with her partner and that the mother was breastfeeding when she entered the program, therefore they received education and support from the interdisciplinary team, which could favor confidence and willingness towards breastfeeding.